Getting Classroom Observations Right - Whitehurst, Grover; Chingos, Matthew M; Lindquist, Katharine (Education next, 2015)
This article contributes to the body of knowledge on teacher evaluation systems by examining the actual design and performance of new teacher-evaluation systems in four school districts that are at the forefront of the effort to evaluate teachers meaningfully. The authors find first that the ratings assigned teachers by the districts' evaluation systems are sufficiently predictive of a teacher's future performance to be used by administrators for high-stakes decisions. While evaluation systems that make use of student test scores, such as value-added methods, have been the focus of much recent debate, only a small fraction of teachers, just one fifth in the four study districts, can be evaluated based on gains in their students' test scores. The other four-fifths of teachers, who are responsible for classes not covered by standardized tests, have to be evaluated some other way, including, in the test districts, by basing the teacher's evaluation score on classroom observations, achievement test gains for the whole school, performance on non-standardized tests chosen and administered by each teacher to their own students, and by some form of "team spirit" rating handed out by administrators. In the four districts studied, classroom observations carry the bulk of the weight, comprising between 50 and 75 percent of the overall evaluation scores for teachers in non-tested grades and subjects. Based on the analysis of system design and practices in the four study districts, the following recommendations are suggested: (1) Teacher evaluations should include two to three annual classroom observations, with at least one of those observations being conducted by a trained observer from outside the teacher's school; (2) Classroom observations that make meaningful distinctions among teachers should carry at least as much weight as test-score gains in determining a teacher's overall evaluation score when both are available; and (3) Most important, districts should adjust teachers' classroom-observation scores for the background characteristics of their students, a factor that can have a substantial and unfair influence on a teacher's evaluation rating.